9.24 THE ROLE AND IMPORTANCE OF THE THEORY OF LAND RENT IN THE SYSTEM OF USE OF LAND RESOURCES - Fayzullaev Zafarjon Sobirjon ugli – PhD student. “Tashkent Institute of Irrigation and Agricultural Mechanization Engineers” National Research University Email: mr.boev.2000@mail.ru (Innovative technologies in construction Scientific Journal, 2024)
The article examined the theory of land rent, the process of land reform, as well as the issues of collecting land taxes, the improvement of the land tax system on factors that shape differential rent and its importance, the tax system during the study, were made on the basis of which proposals and recommendations. Key words: land tax, tax system, land rent, differential rent I, differential rent II, absolute rent, monopoly rent, natural factors, economic factors. Introduction. Form a system of economic regulation of land use-traction requires the development of a methodological mechanism as a theory of land rent, of course. Land rent is primarily an income factor, and its existence is associated with a number of distinctive features of land that cannot be taken into account in sectors of the economy, especially in agriculture [1]. The theory of land rent is an economic doctrine, which consists of two parts: the first part explains the reasons, conditions and source for the occurrence of land rent, separates its types, and the second is related to the issues of distribution of rent [2]. The properties and laws of rent relations developed by the classics of economic theory, the methods of distribution and redistribution of the wealth of society determined through them, have not lost their relevance even today. Therefore, it can and should be used to solve a number of practical issues related to the justification of the economic mechanism of land use, including such important economic concepts as land value, land tax, rent [3]. W. Petty equates rent with added value and interprets it as the result of extra labor. He explains the occurrence of differential rent in relation to the location of land plots and the level of land fertility [4]. Summarizing Petty's land rent earnings, it can be concluded that, firstly, land rent is a part of the product produced with the participation of land, which represents the share of the land in the production of the product (the net product of the land) as a source of income, and, thirdly, the recipient of land rent is the owner of the land [5].